(untitled) (Research, Society and Development, 2021)
The study analyzes the archetypal female figure present in the mythical narratives of Paiter Suruí, an indigenous people residing on the border between the states of Rondônia and Mato Grosso, in Brazil. For this, seven Paiter Suruí narratives presented in the book Vozes de Origem, a collection of stories narrated by Paiter Suruí indigenous peoples in their native language, the tupi-mondé,to the anthropologist Betty Mindlin, responsible for the translation into the Portuguese and organization of the book, are used as the data source. As a theoretical-methodological framework, the Analytical approach of Psychology is used from the concept of symbolic amplification proposed by Carl G. Jung (18751961) and elaborated as a method of analysis by Marie Louise Von Franz (19151998). The analysis course indicates the female archetypes existing in this culture through their mythical narratives, being predominant the Archetype of the Maiden, the Great Mother and the Fatal Woman. According to Analytical Psychology, it can be observed that the mythical indigenous narrative constitutes a coherent and organized sense of meaning about the psyche:unconscious processes are transposed into narratives, in which the female archetypal figure emerges as a representation of the figure of woman in Paiter Suruí society; and the mythical narrative as a representation of the indigenous cultural reality of this ethnicity, as well as a propagation of its values. Based on this assumption, the mythical narratives represent, through symbology, elements of meaning, such as the organization of the Paiter Suruí society, aspects that represent the feminine and the patterns of expected behaviors.